Correlation of the expression of estrogen receptor, progesterone receptor and HER2/neu with the clinical features and the tumour histopathology in patients of breast carcinoma at mahavir cancer sansthan - Lata, Kumari B.; Nirala, Surya K. (International Journal of Research in Medical Sciences, 2021)
Background: Breast carcinoma is the most common malignant tumor and the leading cause of cancer death in women, with more than 10,00,000 cases occurring worldwide annually. Its incidence varies from one geographical area to the other. Methods: Cases of all breast conservative surgeries and modified radical mastectomy specimen received for routine histopathological evaluation from the department of onco Surgery, Mahavir Cancer Sansthan, Patna, Bihar, form the source of data for the study. Results: Infiltrating duct cell carcinoma (NOS) type was the commonest type of carcinoma breast in our institute with significant group occurring in more than 45 years of age. ER and PR positive expression was seen in grade 2 tumors and negative expression was seen with tumor size more than 2cm, positive lymph nodes and higher stage of disease. HER2/neu negative expression was seen in the post-menopausal age group, tumor size more than 2 cm, positive lymph nodes and higher stage of disease indicating bad prognosis. HER2/neu expression was inversely related to ER and PR expression. HER2/neu expression was seen in 50% of medullary carcinoma which is rare. Triple negative cases were seen in 22.08% cases of infiltrating duct cell carcinoma indicating bad prognosis. Conclusions: A beforehand knowledge of these immunohistochemical markers can help oncotherapists to initiate a correct form of treatment and improve the survival rate in breast carcinoma patients.